Solar ultraviolet radiation levels at the university campus of the Universidad Nacional Intercultural Fabiola Salazar Leguía de Bagua, 2019 - Santamaría Baldera, Nemesio (2021)
The city of Bagua is located in the northern part of Peru, on a natural platform on the right bank of the Utcubamba River, at 400 meters above sea level, with an average temperature of 32 °C, where the university city is located. In order to measure UV radiation, a RIKA Electronic Technology Co., Ltd. mini-station, model RK900-05, was installed on the campus of the Universidad Nacional Intercultural Fabiola Salazar Leguía de Bagua, to record data during the period March-November 2019. The data were subjected to a statistical analysis that included, averages, standard deviation and frequency distribution among others. This work shows us the values of UV radiation in the university city finding a radiation ranging between 6000 μW/m2 to 7000 μW/m2 in the months March-April, between 4000 μW/m2 to 6000 μW/m2 in the months May-July, the highest values of UV radiation were recorded in the months of September-November, reaching 6000 μW/m2 and exceeding 8000 μW/m2, these being the hottest months of the year in the city of Bagua.